Design of a New Type of Underactuated Manipulator - Bin Peng; Jiang Gang; Cheng Qian (Jixie chuandong)
According to the demand of clamping the medicine box proposed by the medicine factory,a new design scheme of underactuated manipulator is presented.The pneumatic drive is used in this design scheme of the manipulator,and using the theory of variable degree of freedom and dead center of mechanism,the actions of reliable clamping and lifting to medicine box are realized by using single power source.On this basis,through the structure analysis and calculation of its force,the function of manipulator is analyzed and the theoretical results are actually verified by entity model.The analysis of the manipulator shows that stability performance,large force clamping and the convenience of operation reached the the design requirements.